Context-Aware Web Service Composition based on AI Planning. Issue 1 (2nd January 2017) - Omid, Maryam
ABSTRACT: A web service is an application that is published on the web and can be discovered and used automatically. In many cases, a web service cannot provide the capability that the user has requested. Therefore, according to the user request, it should be possible to combine various services and produce a new composite service for the user request. Context is the information that can be used to characterize the situation of an entity. In this paper, we present our context model for web service composition and implement the newly proposed framework for context-aware web service composition and show how the newly proposed framework reduces the number of failures and composition time.